Penggunaan Obat Herbal pada Responden COVID-19 yang Menjalani Isolasi Mandiri - Mita Restinia; Hendri Aldrat; Alia Dening Pangestuti; Ahmad Musir (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2023)
COVID-19 is an infectious disease caused by spreading the coronavirus worldwide. In Indonesia, COVID-19 patients with mild symptoms can undergo independent isolation at home. The public widely uses herbal medicines in the treatment of COVID-19. A non-experimental cross-sectional study was performed to identify the profile of the use of herbal medicines by COVID-19 respondents during independent isolation in South Tangerang. The sampling technique conducted purposive sampling on 96 respondents who met the inclusion criteria. The instrument used is a questionnaire with close-formatted and open-ended questions. Questionnaires were distributed online from March to May 2022. The most used herbal medicines were honey (85.4%), ginger (52.1%), propolis (35.4%), turmeric (32.3%) and garlic (26%). The reason respondents used herbs because they were made from natural ingredients (84.4%), the method of use was boiled or brewed (58.3%), information on the use of herbal medicines was obtained from the family (63.5%), the source of obtaining herbal medicines was sent by relatives/family/friends (69.8%), the duration of using herbal medicines is 1-7 days (39.6%), the time to use herbal medicines was generally in the morning (49%), and the cost of herbal medicines is IDR 100,000 - 500,000 (44.8%). Through this research, it can be concluded that South Tangerang City's people still use herbal medicines as an alternative treatment while infected with COVID-19. Therefore, further education on the safety and maximum use of herbal medicines is required.